152k views
3 votes
Simplify the expression: (6 + 4i) − (5 + i). 1 + 3i 1 + 5i 11 + 3i 11 + 5i

2 Answers

3 votes

Answer:

1+3i

Explanation:

(6+4i)-(5+i)

6+4i-5-i

1+4i-i

1+3i

User Anderson K
by
6.0k points
4 votes

Answer: 1+3i

Explanation:

(6 + 4i) − (5 + i)

Before solving further, note that :

Minus × Minus = Plus

Plus × Minus = Minus

Plus × Plus = Plus

(6 + 4i) − (5 + i)

Open the bracket

= 6 + 4i - 5 - i

Collect like terms

= 6 - 5 + 4i - I

= 1 + 3i

User Superkinhluan
by
5.2k points